Acoustic properties of highly elastic polyurethane foam vapen HR 3744 - Pajović, Stefan; Radičević, Branko; Miodragović, Tanja; Perić, Jovana (Journal of Production Engineering, 2023)
Within this research, testing of the acoustic properties of polyurethane foam samples was conducted. The measurement of the absorption coefficient was performed using the transfer function method in an impedance tube, according to the SRPS EN ISO 10534-2:2008 standard. The tested samples represent highly elastic polyurethane foam of low density, with sample thickness ranging from 10 mm to 100 mm. The research results indicate the potential application of polyurethane foam in areas that require efficient sound insulation or noise control, particularly in the mid-frequency range. Therefore, polyurethane foam can be considered an excellent material with acoustic properties that exceed expectations within the given frequency range.